Hearing things in music for films: music, fiction and engagement - Birger Langkjær (SoundEffects, 2013)
Film music is often thought of as something that adds to the visuals. Yet, this truism somehow obscures the complexity of how film music works. First, music has no single and fixed meaning that can be added to the visuals in the first place. Second, experiencing audiovisual meaning can be accounted for on several levels. For that reason this article proposes eight different but complementary ways of listening to music along the lines of ecological theories of musical perception in which it is argued that we hear things, that is, referential matters in music. The validity of this is demonstrated through the discussion of a series of scholarly interpretations of John Williams’ music for the opening scene of Jaws (1975). Second, it is argued that music may add meaning on different levels and a three level model of film music analysis is suggested in which the music as an expressive device, the fiction world as a dramatic space and kinds of audience engagement are conceived as three separate, yet interacting, levels of the filmic experience.